An Effective Error Correction Scheme for Arithmetic Coding. (5th July 2015) - Lin, Qiuzhen; Wong, Kwok-Wo; Li, Ming; Chen, Jianyong
Abstract : We propose an effective error correction technique for arithmetic coding with forbidden symbol. By predicting the occurrence of the subsequent forbidden symbols, the forbidden region is actually expanded and theoretically, a better error correction performance can be achieved. Moreover, a generalized stack algorithm is exploited to detect the forbidden symbol beforehand. The proposed approach is combined with the maximum a posteriori (MAP) metric to keep the highly probable decoding paths in the stack. Simulation results justify that our scheme performs better than the existing MAP methods on the error correction performance, especially at a low coding rate.